Immunogenicity and Contraceptive Efficacy of Escherichia coli‐Expressed Recombinant Porcine Zona Pellucida Proteins. (27th February 2013) - Gupta, Neha; Chakrabarti, Kausiki; Prakash, Krishna; Wadhwa, Neerja; Gupta, Tripti; Gupta, Satish K.
Abstract : Problem: To overcome availability of the purified native zona pellucida (ZP) glycoproteins for immunocontraception, porcine ZP3, and ZP4 were expressed in E. coli . Method of study: Purified recombinant proteins were characterized by SDS‐PAGE and Western blot, and immunogenicity and contraceptive efficacy determined in FvB/J female mice. Results: Purified ZP3, ZP3 with promiscuous T‐cell epitope of tetanus toxoid, ZP4 and ZP4 incorporating promiscuous T‐cell epitope of bovine RNase revealed 44‐, 49‐, 53‐, and 55‐kDa bands by SDS‐PAGE and Western blot, respectively. Immunization of female mice with recombinant proteins elicited high antibody titers as well as T‐cell responses. Immune sera recognized mouse oocyte ZP and also inhibited in vitro fertilization. Immunized mice showed significant decrease in fertility. Recombinant proteins were able to recall memory antibody response in female mice primed with porcine native ZP. Conclusion: Availability of recombinant porcine proteins will be useful in the development of contraceptive vaccine.